HUBUNGAN PELAKSANAAN PENDIDIKAN EMPAT PILAR MANAJEMEN DIABETES MELLITUS (DM) DI KOTA PEKANBARU DENGAN PENGETAHUAN TENTANG PASIEN DM - Yurnalis Yurnalis; Sofiana Nurchayati; Erwin Erwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Diabetes mellitus (DM) is a degenerative disease that can cause complications. Handling of DM patients is done with 4 pillars, including: Education, diet, physical exercise, and treatment. The purpose of this study was to determine the relationship of nurses' knowledge about the implementation of management education with knowledge of DM in the Pekanbaru City Health Center Area. The research design used is descriptive correlation with cross sectional approach. The sampling technique in this study is total sampling with 30 respondents. Univariate analysis results based on the level of patient knowledge about DM management about good education (96.7%), good diet (80%), good exercise (86.7%) in the treatment category (93.3%) in the good category . Respondents' knowledge about DM management is sufficient (53.3%), the results of bivariate analysis obtained p value > α (0.05), it was concluded that there was no relationship between the implementation of the four pillars of DM management with knowledge of DM. The role of nurses as educators in patients with DM in the health center is not optimal. It is recommended that the role of educator be given training in developing education of the four pillars of sustainable management in health services.Keywords: DM Management, Implementation, Knowledge